Penerapan Aplikasi Android Dalam Pengelolaan Transaksi Usaha Mikro - Yasir Hasan (Journal of Social Responsibility Projects by Higher Education Forum, 2020)
Micro business owners do not think too much about the recapitulation of transaction activities and data processing of their businesses. The application of computer technology in managing transactions or information systems is considered an expensive and complicated technology. This is certainly considered to only be a very large fund in the application of technology. The use of android technology in the community to manage business is very rarely found. Though for the use of Android smartphones in Indonesia is very much. Prices of Android smartphone devices are also known to be affordable and have high hardware and software system specifications. Enterprises in helping micro business owners to be able to do the documentation of the business by applying computer technology based on Android smartphones. This application can help micro businesses in the middle to lower economic community